ANALISIS INKLUSI KEUANGAN SYARIAH DAN INVESTASI INDUSTRI HALAL TERHADAP PENGEMBANGAN INDUSTRI HALAL DI INDONESIA - Amalia, Trisia; Sumengkar, Apung; Kusumaningrum, Ria (ALAMIAH : Jurnal Muamalah dan Ekonomi Syariah, 2025)
The halal industri is a strategic sector that has great potential in driving national economic growth, especially in countries with a Muslim majority population like Indonesia. Sharia financial inclusion is one of the important prerequisites in expanding public access to financial services that comply with sharia principles, while investment in the halal sector is considered capable of increasing production capacity, innovation, and the competitiveness of the domestic halal industri. The purpose of this study is to determine the Effect of Sharia Financial Inclusion and the Halal Industri on the Development of the Halal Industri in Indonesia. This type of research is quantitative research using secondary data obtained from primary data in the form of Sharia financial data and halal industri investment in 2021-2024 from the Financial Services Authority. The analysis method used in this study is the Multiple Linear Regression method processed using SPSS Version 26. The results of the study show that increasing sharia financial inclusion contributes positively to the development of the halal industri through expanding access to financing, insurance, and sharia investment for business actors. In addition, increasing investment in the halal industri has a significant impact on expanding production capacity, distribution, and innovation of halal products. Both variables have a synergistic relationship and mutually reinforce each other in creating a conducive ecosystem for sustainable halal industri growth. This finding underlines the importance of a strategy to strengthen Islamic financial inclusion and increase investment to strengthen the competitiveness of the halal economy in Indonesia.